2019
DOI: 10.1002/jlb.ma0718-295rr
|View full text |Cite
|
Sign up to set email alerts
|

Real-time deformability cytometry reveals sequential contraction and expansion during neutrophil priming

Abstract: It has become increasingly apparent that the biomechanical properties of neutrophils impact on their trafficking through the circulation and in particularly through the pulmonary capillary bed. The retention of polarized or shape‐changed neutrophils in the lungs was recently proposed to contribute to acute respiratory distress syndrome pathogenesis. Accordingly, this study tested the hypothesis that neutrophil priming is coupled to morpho‐rheological (MORE) changes capable of altering cell function. We employ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 54 publications
(120 reference statements)
3
30
0
1
Order By: Relevance
“…RT‐DC revealed that neutrophil priming via several different stimuli induces a common series of phenotypic changes, with an initial phase of contraction and stiffening lasting 1–5 min, followed by a phase of expansion and increased deformability achieved within 15–30 min post‐priming. Neutrophils simultaneously became shape changed in a matter of seconds but returned to their original morphologic phenotype within 2–5 h [Bashant et al., ]. This finding aligns with previous reports of neutrophil “de‐priming” [Kitchen et al., ; Ekpenyong et al., ].…”
Section: Mechanics In Immunologic Function Of Myeloid Cellssupporting
confidence: 90%
See 3 more Smart Citations
“…RT‐DC revealed that neutrophil priming via several different stimuli induces a common series of phenotypic changes, with an initial phase of contraction and stiffening lasting 1–5 min, followed by a phase of expansion and increased deformability achieved within 15–30 min post‐priming. Neutrophils simultaneously became shape changed in a matter of seconds but returned to their original morphologic phenotype within 2–5 h [Bashant et al., ]. This finding aligns with previous reports of neutrophil “de‐priming” [Kitchen et al., ; Ekpenyong et al., ].…”
Section: Mechanics In Immunologic Function Of Myeloid Cellssupporting
confidence: 90%
“…This finding aligns with previous reports of neutrophil “de‐priming” [Kitchen et al., ; Ekpenyong et al., ]. Thus, high‐throughput DC demonstrated primed neutrophils could be stiffer or softer depending on the time frame at which cells were analysed [Bashant et al., ]. Similarly, in the context of macrophages and dendritic cells, some inflammatory mediators have been reported to stiffen cells while others have the opposite effect [Bufi et al., ].…”
Section: Mechanics In Immunologic Function Of Myeloid Cellssupporting
confidence: 90%
See 2 more Smart Citations
“…Since F-actin has been shown to bind to activated TRPV4, it can be speculated that this priming/depriming occurs as a function of TRPV4 activation secondary to the formation of F-actin rims (24). Given the implications of such mechanical effects due to e.g., changes in neutrophil shape and stiffness not only on neutrophil kinetics through the vascular system but also on their biological responsiveness in health and disease (86), the molecular dissection of the underlying signaling pathways and the potential link to TRPV4 mechanosensation may be of considerable scientific interest and relevance. Shear stress in the vasculature is a result of blood flow velocity, vessel diameter, and blood viscosity and primarily acts on endothelial cells outlining the vessel lumen.…”
Section: Trpv4 In Mechanosensation Of Immune Cellsmentioning
confidence: 99%